Bolivia : 2011 Article IV Consultation-Staff Report; Supplement and Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bolivia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Bolivia showed a solid macroeconomic performance in recent years, owing to its strong trade and prudent economic policies. IMF staff stressed the need to tighten monetary conditions through increasing the policy interest rate as a means to combat inflation. The Executive Board praised authorities for their sound macroeconomic management, and concurred that structural reform and increased investment will enhance economic growth. However, the crisis management framework could be strengthened with a deposit insurance scheme to protect small depositors in the event of bank liquidation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet